Mentoría de menores y jóvenes : guía práctica - Dolan, Pat, 1958-; Brady, Bernadine (Narcea sociocultural., 2015)
Youth mentoring can be an effective way of supporting troubled youngsters, helping them sustain positive mental health, cope with stress, and lead successful lives through adolescence and into adulthood. This is a guide to mentoring programmes, showing how, if managed well, they can increase the social support available to young people.